Prognosis and diagnosis of reproductive disorders associated with genital tuberculosis in women - O. Y. Leshchenko; A. V. Atalyan; A. B. Malanova (Acta Biomedica Scientifica, 2018)
Diagnosis of tuberculosis of female genitalia is based on a complex of traditional and new diagnostic methods used in a certain sequence in outpatient and/or inpatient settings. Because of insufficiently effective diagnostic tests, genital tuberculosis is often detected in irreversible anatomical changes, when the prospects for restoring the reproductive function are unsatisfactory. The aim of the work was to identify socio-economic and biomedical risk factors for reproductive disorders associated with genital tuberculosis in order to create statistical models for the prediction and diagnosis of these disorders. To study the connection between the presence of genital tuberculosis and a number of prognostic and diagnostic features, the method of nonlinear regression analysis (logistic regression) was used. Statistical models of prognosis and diagnosis of reproductive disorders associated with genital tuberculosis (HT) in women at the outpatient stage are proposed. The forecast model included clinical and anamnestic predictors: prolonged subfebrile condition, weight loss, increase in inguinal lymph nodes, membership in the social group «female students», contact with tuberculosis patients, tuberculin specimen turnover, presence of pulmonary tuberculosis in the anamnesis. The statistical diagnostic model included the following important methods: enzyme immunoassay, laser fluorescence method, Diaskin-test, hysterosalpingography (segmented fallopian tubes), determination of progesterone, estradiol and testosterone levels in the blood serum (decrease of these hormones).